Effect of short and long-term storage on essential oil content and composition of cinnamon (Cinnamomum verum Bercht. & Presl.) leaves - P N Kaul, A K Bhattacharya, A A Naqvi, B R Rajeswara Rao, D K Rajput, (Journal of Spices and Aromatic Crops, 2006)
The effect of duration of storage of cinnamon (Cinnamomum verum) leaves on the content andchemical composition of essential oil was studied. The results revealed that neither the es-sential oil content (1.9%-2.2%), nor the chemical composition of essential oil (eugenol 87.1%-90.7%; eugenyl acetate 2.9%-5.5%; linalool 0.8%-1.2%; benzyl benzoate 0.3%-0.6%) wasaffected during the storage of leaves for up to 15 months.